Factors influencing job satisfaction among medical surgeon specialist s in public Hospitals in Southern Malaysia - Nurul Hanany, A Rahman (2018)
This study investigated the factors that influencing job satisfaction among medical specialist in public hospital, Southern Malaysia between rewards, management and resource availability. A total of 48 questionnaires were personally distributed to the respondents in the public hospital within southern areas which are Negeri Sembilan, Malacca and Johor. From the 48 questionnaires distributed, 42 questionnaires were returned, representing a response rate of 85%. The hypotheses for direct effect were tested using multiple regression analysis, and data was also analysed for data screening, descriptive, factors and correlation analysis. The result shows that rewards and resource availability have influence with job satisfaction while management do not have influence with job satisfaction among medical specialists in public hospitals in Southern Malaysia.